Effect of hydrolysis enzymatic time on the techno-functional properties and antioxidant capacity of jumbo squid Dosidicus gigas - Flores Anaya, Santos Maximino (2020)
Muscle proteins of Dosidicus gigas mantle have great techno-functional advantages and during their processing at industrial level considerable discards of muscle proteins are generated and used to elaborate meals with low added value. The aim of the study was to evaluate the effect of hydrolysis time on the techno-functional properties and antioxidant capacity of jumbo squid. Mantle muscle protein discards were cooked, ground and subjected to enzymatic hydrolysis (Protamex ©) for 1, 2, 3, 4, 5 and 6 hours at 58 ° C; ratio of water: substrate 1: 1. The hydrolysis reaction was stopped at 90 ° C for 5 minutes and then were filtrate. Hydrolyzed solutions (2% of dissolved solids) in established times were taken and their techno-functional properties such as foaming, emulsifying, antioxidant capacity and degree of hydrolysis were determined. The hydrolysis reaction was stopped at 90 °C for 5 minutes and then samples were filtered. Foaming property was increased significantly from 27,4 ± 2,5% (0 hours) to 96,2 ± 5,0% (6 hours). The emulsifying property was decreased significantly from 84,1 ± 3,6% (0 hours) to 56,3 ± 3,2% (6 hours). Antioxidant property showed significant differences at 5 and 6 hours, which showed inhibition of the DPPH radical in the order of 15 to 20% of the initial concentration. The degree of hydrolysis was increased significantly until 18,4 ± 0,6% (6 hours). Discards from jumbo squid muscle mantle proteins presented techno-functional advantages that could serve as foaming food agents, protein inputs with emulsifying and antioxidant properties for formulation of restructured meats such as sausages, hamburgers that allow to improve palatability and shelf life.